Assessment of latent tuberculosis infection in Takayasu arteritis with tuberculin skin test and Quantiferon-TB Gold test - DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2010)
A possible relationship between Takayasu arteritis (TA) and tuberculosis (TB) has been suggested. An increased frequency of tuberculin skin test (TST) was observed in TA patients. Quantiferon-TB Gold test (QFT) is a new in vitro assay measuring interferon-gamma response to M. tuberculosis antigens and helpful in diagnosing latent TB infection. The aim of this study was to investigate latent TB infection among TA patients by the use of both TST and QFT Gold test. Ninety-four (male/female: 7/87) TA patients fulfilling ACR 1990 TA criteria from three different university hospitals in Turkey and 107 control subjects without inflammatory diseases were included in the study. Data about medical history (TA and TB) were collected for both groups. TST and QFT were performed. TST values a parts per thousand yen5 mm for TA patients and a parts per thousand yen15 mm for controls was accepted as TST positivity. Even though TA group was older (40 +/- A 12 vs. 32 +/- A 8, P < 0.001), there was no significant difference between TA patients and controls regarding demographic characteristics. Six TA patients and one control had a history of previous TB infection (P = 0.054). Although TST positivity was higher in TA group [55 patients (62.5%) vs. 24 controls (41.4%), P = 0.008], QFT positivity was similar between two groups [21 patients (22.3%) vs. 24 controls (22.4%), P > 0.05]. QFT was negative in two of six TA patients with previous TB history. Rate of latent TB infection in TA patients measured with QFT is no more than controls. QFT seems to be a good and favorable test compared with TST in detecting LTBI in TA.
Keywords: Tuberculosis; Takayasu arteritis; Tuberculin skin test; Quantiferon-TB Gold test; INTERFERON-GAMMA ASSAY; AUTOIMMUNE-DISEASES; THERAPY; TOOLS